The left hand of God - Hoffman, Paul (London Razorbill, 2011)
YA. Fantasy fiction. 'Listen. The Sanctuary of the Redeemers is named after a damned lie for there is no redemption that goes on there and less sanctuary.' The Sanctuary of the Redeemers: vast, desolate, hopeless. Where children endure brutal cruelty and violence in the name of the One True Faith. Lost in the Sanctuary's huge maze of corridors is a boy: his age uncertain, his real name unknown. They call him Cale
1
Keywords: Prisons -- Fiction; Young men -- Fiction